1997
DOI: 10.1113/expphysiol.1997.sp004054
|View full text |Cite
|
Sign up to set email alerts
|

Calcium paradox in guinea‐pig ventricular myocytes

Abstract: SUMMARYMeasurement of the release of lactate dehydrogenase (LDH), the development of contracture and the exclusion of the dye Trypan Blue were made in isolated guinea-pig ventricular myocytes subjected to conditions that evoke a calcium paradox in intact heart. Incubation at 25°C reduced the release of LDH associated with mechanical manipulation of the myocytes so that during prolonged incubation in media free of Ca2' and Mg2+ ions at 25°C little release of LDH occurred.A significant release of LDH into the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Although Piper et al [42] have shown that that Ca 2+ -paradox does not occur in cardiomyocytes unlike isolated heart, others have established the existence of Ca 2+ -paradox in cardiomyoctes [43]. The occurrence of Ca 2+ -paradox in the present study was evident from the observation that a significant reduction in the number of rod shape cardiomyocytes and their ability to exclude trypan blue after Ca 2+ -repletion was observed in accordance with the previous studies [44]. While, the potential importance of cell death due to apoptosis by increase in [Ca 2+ ] i is not fully understood, an increase in [Ca 2+ ] i as a stimulus for apoptotic cell death has been demonstrated in lymphoid cells, leukemic T-cells and cytotoxic T-cells [7].…”
Section: Discussionsupporting
confidence: 93%
“…Although Piper et al [42] have shown that that Ca 2+ -paradox does not occur in cardiomyocytes unlike isolated heart, others have established the existence of Ca 2+ -paradox in cardiomyoctes [43]. The occurrence of Ca 2+ -paradox in the present study was evident from the observation that a significant reduction in the number of rod shape cardiomyocytes and their ability to exclude trypan blue after Ca 2+ -repletion was observed in accordance with the previous studies [44]. While, the potential importance of cell death due to apoptosis by increase in [Ca 2+ ] i is not fully understood, an increase in [Ca 2+ ] i as a stimulus for apoptotic cell death has been demonstrated in lymphoid cells, leukemic T-cells and cytotoxic T-cells [7].…”
Section: Discussionsupporting
confidence: 93%